Structure, vibrational and electronic spectra, and bonding in trans-diaquabis(oxalato)vanadate(III) complex salts, A[V(ox)2(H2O)2]·xH2O (A = Cs, K, or NH3Me), and the X-ray crystal structure of the potassium salt (x= 3) - Stranger, Robert; Sirat, Kamaliah; Smith, Peter W. (Royal Society of Chemistry Publishing, 1988)
The X-ray crystal structure of potassium diaquabis(oxalato)vanadate(III), K[V(ox)₂(H₂0)2].3H₂0, has been determined [monoclinic, space group P2/c, with unit-cell parameters a = 7.971 (4), b = 5.691 (2), c = 14.167(5) A, β = 108.97(3)", and Z = 2]. The structure has been refined to an R value of 0.032 using 560 independent reflections. In comparison with the corresponding Cs⁺ and NH₃Me⁺ salts, the K⁺ salt exhibits a significantly longer bond distance for axially co-ordinated water and this is manifested in band shifts of 500-1 000 cm ⁻¹ in the visible region. For all three salts vibrational spectra and single-crystal polarised electronic spectra are reported together with assignments. Analysis of the ligand-field spectra is presented in terms of the angular overlap model. It is shown that the band shifts occurring in the electronic spectrum of the K⁺ salt can be reproduced by a reduction in the cr-bonding capacity of the co-ordinated water together with a slight increase in the c bonding of the oxalate ligand, both of which areconsistent with structural differences existing between the K⁺ and the other two salts. Significant anisotropy exists in the metal- oxalate IT interaction with the in-plane contribution relatively small. In addition, anomalous temperature-dependent bands resulting from vibronic coupling with internal O-H stretching vibrations are present in the electronic spectra of both the Cs⁺and NH₂Me⁺ salts